Step 1: Set the two equations equal to each other and solve for x.
3x -5 = 6x - 8
3x + (-5+5) = 6x -8 + 5
(3x - 6x) = (6x - 6x) - 3
-3x/-3 = -3/-3
x = 1
Step 2: To solve for y take one of the given equation of your choice (for the purpose of this explanation I will only do y = 3x - 5) and replace x with 1, then solve for y
y = 3(1) - 5
y = 3 - 5
y = -2
(1,-2)
Check:
-2 = 3(1) - 5 ---> - 2 = -2
-2 = 6(1) - 8 ---> -2 = -2
Hope this helped!
It is not a function—an element from the domain is paired with more than one element from the range. Specifically, the input value of 4 corresponds to two output values: 5 and -4.
A function can only take on one output for each input. It only takes one input value to associate with more than one output value to be invalid as a function.
Please mark this answer as the Brainliest, if you find this helpful :)
4.5 • 10-5 = 40
2.4 • 10-2 = 22
Answer:
x = -2.5
x = 2
Step-by-step explanation:
Hello!
We can remove the denominators by multiplying everything by it.
Solve:
Let's make one side equal to 0.
Solve by factoring, and then the zero product property.
Multiply 2 and -10. You get -20. Think of two number that multiply to -20, and add to 1. If we think about the standard form of a quadratic,
, think two numbers that equal "ac" and add up to "b".
Using the zero product property, set each factor to 0 and solve for x.
- 2x + 5 = 0
2x = -5
x = -5/2 = -2.5 - x - 2 = 0
x = 2
The two answers are x = -2.5, and x = 2.